2006
DOI: 10.4161/cbt.5.5.2657
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of hemangioblastoma cyst fluid

Abstract: Intratumoral hemangioblastoma cyst fluid originates from serum. Cyst formation associated with hemangioblastoma, whether peri- or intratumoral, is a consequence of vascular leakage. Anti-VEGF therapy may effectively control hemangioblastoma cyst formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Hemangioblastomas, despite their benign histological appearance (10, 30-32, 53, 94), can cause symptoms through mass effect and edema related to cyst formation and development (54, 55, 96, 99). The contents of the hemangioblastoma cyst have always been controversial.…”
Section: Insights Into Neurological Diseases From Proteomicsmentioning
confidence: 99%
“…Hemangioblastomas, despite their benign histological appearance (10, 30-32, 53, 94), can cause symptoms through mass effect and edema related to cyst formation and development (54, 55, 96, 99). The contents of the hemangioblastoma cyst have always been controversial.…”
Section: Insights Into Neurological Diseases From Proteomicsmentioning
confidence: 99%
“…6,[9][10][11] We did not evaluate the biochemical composition of peritumoral cystic fluid associated with pituitary macroadenoma and the operating surgeon did not notice a proteinaceous or xanthochromic fluid during the course of resection. All macroadenomas were resected transsphenoidally, either as primary resection or in the initial approach, so observation of the surrounding peritumoral cysts and the response to surgical decompression was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…A HBL presenting as a solid nodule can grow in size but can also rapidly develop into one or multiple cysts in or around the nodule even in patients without VHL. Emerging proteomic analysis data have shown that cyst formation associated with HBL, whether peritumoural or intratumoural, is a consequence of vascular leakage secondary to upregulation of vascular endothelial growth factor (VEGF); and anti-VEGF therapy may effectively control cyst formation 9. Initially, the extravasation of fluid produces a small region of oedema surrounding the tumour and equilibrium is achieved.…”
Section: Discussionmentioning
confidence: 99%